The human right to housing and the expansion of housing policies applied to the case of Residential Cristo Lives in Tucuruí (PA) - Amaro Correia, Marília (2023)
This article aims to analyze how housing policies in Brazil have been implemented, their effectiveness and contradictions in combating the housing deficit and how they have responded to the criteria of adequate housing, in an Amazonian context. The research was developed through an interdisciplinary study between Law and Social Sciences, having as a theoretical apparatus, in addition to the literature on the right to the city, financialization of home ownership, and the performance of housing policies, the legal documents attached to the process of occupation of the Residencial Cristo Vive, located in the municipality of Tucuruí, in the state of Pará, which is affected by the developmental policies of expansion of capital in the Amazon. It was noticed that housing policies serve the financial and real estate sector, inverting values in relation to social rights and that the concentration of housing policy only in the focus of the acquisition of private property, ended up making it difficult for people to access to decent housing.